Methods of previous coding, that uses in systems of radio special purpose with Massive-MIMO technology - Romanenko, Igor; Shyshatskyi, Andrii; Kuvshinov, Olexiy; Pikul, Rostislav (НТУ "ХПІ", 2018)
Modern radiocommunication systems of special purpose function in the conditions of shortage of radio resources and active radio-electronic suppression. One of the ways to increase noise immunity, bandwidth and capacity of communication networks is using antenna arrays, namely, Massive-MIMO technology. However, the possibilities of this technology are not used in full. In order to increase the efficiency of the using of Massive-MIMO technology, the authors of this article are considered methods of pre-coding. The analysis is intended to decompose existing methods of pre-coding for the further development of highly effective algorithms of pre-coding. In the above scientific work, the authors of the article uses the basic provisions of the theory of communication, the theory of signals, the theory of noise immunity, as well as the theory of antennas. According to the results of the research, the authors draw the following conclusions: the matrices of the previous coding, which have the same right singular vectors, which are the optimal for all criteria; the main difference between the previous coding algorithms, that can be obtained by various synthesis criteria is the different distribution of the radiated power between the spatial rays. Thus, the analysis showed, that thanks to the identical structure of the work of linear pre-coders, it is possible to carry out a dynamic change on the transmission side of the type of the linear pre-coder, thereby adaptively modifying the characteristics of the transmission and transmission path, while remaining within the framework of practically one structure of the communication channel.

Сучасні системи радіозв’язку спеціального призначення функціонують в умовах дефіциту радіоресурсу та активного радіоелектронного подавлення. Одним з шляхів підвищення завадозахищеності, пропускної здатності та ємності мереж зв’язку є використання антенних масивів, а саме технології Massive-MIMO. Проте можливості зазначеної технології використовуються не в повному обсязі. З метою підвищення ефективності використання технології Massive-MIMO авторами зазначеної статті розглянуті методи попереднього кодування. Зазначений аналіз має на меті провести декомпозицію існуючих методів попереднього кодування для подальшої розробки високоефективних алгоритмів попереднього кодування. В зазначеній науковій праці авторами статті використані основні положення теорії зв’язку, теорії сигналів, теорії завадозахищеності, а також теорії антен. За результатами дослідження авторами зроблені наступні висновки: матриці попереднього кодування, що оптимальні по всіх критеріях мають одні й ті ж самі праві сингулярні вектори; основна відмінність між алгоритмами попереднього кодування, які можливо отримати за допомогою різних критеріїв синтезу, полягає в різному розподілі випромінюваної потужності між просторовими променями. Таким чином, проведений аналіз показав, що завдяки однаковій структурі розглянутих у роботі лінійних попередніх кодерів, можливо проводити динамічну зміну на передавальній стороні типу лінійного попереднього кодеру, тим самим адаптивно змінювати характеристики приймально-передавального тракту, при цьому лишаючись в рамках практично однієї структури каналу зв’язку.
Методи попереднього кодування, що використовуються у системах радіозв’язку спеціального призначення з технологією Massive-MIMO
Keywords: signaling situation; multiple input; multiple output; pre-coding; сигнальна обстановка